Functional Connectivity Networks in Asymptomatic and Symptomatic DYT1 Carriers. Issue 11 (25th July 2016) - Premi, Enrico; Diano, Matteo; Gazzina, Stefano; Cauda, Franco; Gualeni, Vera; Tinazzi, Michele; Fiorio, Mirta; Liberini, Paolo; Lazzarini, Clara; Archetti, Silvana; Biasotto, Giorgio; Turla, Marinella; et al.
ABSTRACT: Background: DYT1 mutation is characterized by focal to generalized dystonia and incomplete penetrance. To explore the complex perturbations in the different neural networks and the mutual interactions among them, we studied symptomatic and asymptomatic DTY1 mutation carriers by resting‐state functional MRI. Methods: A total of 7 symptomatic DYT1, 10 asymptomatic DYT1, and 26 healthy controls were considered. Resting‐state functional MRI (Oxford Centre for Functional MRI of the Brain) [FMRIB] Software Library) (FSL) MELODIC, dual regression, (as a toolbox of FSL, with Nets is referred to "networks") (FSLNets) (http://fsl.fmrib.ox.ac.uk/fsl/fslwiki/FSLNets ) was performed on 9 resting‐state neural networks. Results: DYT1 mutation signature (symptomatic DYT1 and asymptomatic DYT1 ) was characterized by increased connectivity in the dorsal attention network and in the left fronto‐parietal network. Functional correlates of symptomatic DYT1 patients (symptomatic DYT1 vs healthy controls) showed increased connectivity in the sensorimotor network. Discussion: This study argues that DYT1 dystonia is a network disorder, with crucial nodes in sensory‐motor integration of posterior parietal structures. A better characterization of cortical networks involved in dystonia is crucial for possible neurophysiological therapeutic interventions. © 2016 International Parkinson and Movement Disorder Society